Dampak Tanaman Transgenik Bt terhadap Populasi Serangga Pengendali Hayati - Bahagiawati A. Husin (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2005)
An alternative technique to improve plant resistance to insect pests is plant transformation using the genetic engineering technology. Several transgenic plants resistant to insect have been produced and commercially released to environment in some industrial and developing countries. Before release, transgenic plants need to be assessed for their potential risks to human health and environment. One of the environmental risk assessments is the potential risk to non-target insects, including the biocontrol insects. Laboratories, glasshouse, and field experiments have been conducting the study of the impact of transgenic plant resistance to insect, especially transgenic Bt plants to the population of predators and parasitoids. However the results were controversial. The objective of this review is to inform some of controversial results, and to suggest serial experiments need to be done to solve the problem. The impact of the transgenic plant resistance to insects depends on several factors, such as genes that are used to transform the plants, the kind of plant pests, and the kind and stages of the insect natural enemies. Results of the experiments were influenced by sites of the experiments (laboratory, glasshouse, or field) and contact of the natural enemies to the toxin. Some experiments showed that the transgenic Bt plants have no impact to the natural enemies population, and otherwise. Due to the controversial results, the experiment and assessment should be done in depth and carefully studied. A sequential experiments need to be adopted to avoid the misleading interpretation, and the assessment need to be based on a case by case study.